2010
DOI: 10.1111/j.1440-1681.2010.05376.x
|View full text |Cite
|
Sign up to set email alerts
|

Linear regression analysis for comparing two measurers or methods of measurement: But which regression?

Abstract: 1. There are two reasons for wanting to compare measurers or methods of measurement. One is to calibrate one method or measurer against another; the other is to detect bias. Fixed bias is present when one method gives higher (or lower) values across the whole range of measurement. Proportional bias is present when one method gives values that diverge progressively from those of the other. 2. Linear regression analysis is a popular method for comparing methods of measurement, but the familiar ordinary least squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
157
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(171 citation statements)
references
References 51 publications
2
157
1
5
Order By: Relevance
“…Ordinary least-squares regression analysis and analysis of covariance were used to determine whether the linear relationships between PO 2 and current changed during the period of implantation (28). Between animal means Ϯ SE of PO2 measured over each 24-h period were calculated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ordinary least-squares regression analysis and analysis of covariance were used to determine whether the linear relationships between PO 2 and current changed during the period of implantation (28). Between animal means Ϯ SE of PO2 measured over each 24-h period were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Absolute changes in kidney PO2 from both systems were compared using the ordinary least products regression method, using a loss function to obtain 95% confidence intervals. This method for comparing methods of measurement has the benefit of distinguishing between fixed and proportional bias (28). ANOVA was also used to test for systematic bias, between the two methods of measurement, across the five levels of inspired oxygen (10,18,21,40, and 80%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Linear models have been shown to be effective, however, there are deficiencies when there is large differences in variability between groups, which may be relevant when examining -omics data from different types of platforms and/ or data from humans or non-experimental model systems. It has been shown that large variability results in incorrect slope estimates (Cornbleet and Gochman, 1979;Ludbrook, 2010). Furthermore, slope estimates can be different depending on what feature is considered the dependent or independent variable in the linear model.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 We conducted these analyses using R . 9 Using an SGI cutoff of 10 units, 6 we estimated k between each new reader and the control reader (SAS/STAT software package, version 9.2 of the SAS System for Windows XP; SAS Institute Inc).…”
Section: Interreader and Intrareader Validitymentioning
confidence: 99%